Chemotherapy related changes in cfDNA levels in squamous non-small cell lung cancer: correlation with symptom scores and radiological responses - Nithiyanandan Ravi; Parul Gupta; Amanjit Bal; Kuruswamy Thurai Prasad; Mandeep Garg; Rakesh Kapoor; Navneet Singh (Open Exploration Publishing Inc., 2024)
Aim: There is limited data on prognostic value of baseline plasma cell free DNA (cfDNA) in advanced squamous non-small cell lung cancer (sq-NSCLC). This prospective observational study aimed to assess change in plasma cfDNA levels in locally-advanced/metastatic sq-NSCLC with chemotherapy and its correlation with symptom-scores and radiological-responses. Methods: Chemotherapy-naive patients with stages-IIIB/IIIC/IV sq-NSCLC (n = 59), smokers with chronic obstructive pulmonary disease [COPD, COPD-controls (CC); n = 27] and healthy-controls (n = 25) were enrolled. Respiratory symptom burden (RSB) and total symptom burden (TSB) were calculated from mean visual-analog-scores (VAS) of dyspnoea, cough, chest pain, hemoptysis RSB, anorexia and fatigue (all six for TSB). cfDNA was isolated from peripheral blood. All patients received platinum-doublet chemotherapy. RSB/TSB/cfDNA assessment and contrast-enhanced computed tomography (CECT)-thorax scans were done at baseline and post-chemotherapy. Results: At baseline, 13/59 (22%) sq-NSCLC, 3/27 (11%) CC and none (0%) healthy-controls had detectable cfDNA. All three CC were heavy smokers with no evidence of malignancy and undetectable cfDNA levels on repeat testing. In sq-NSCLC group, majority were males (95%), current-smokers (88%), heavy-smokers (70%), had metastatic disease (59%) with median age of 65 years. Eastern Co-operative Oncology Group (ECOG) performance status (PS) was 0-1 (56%) and 2 (42%). Median RSB- and TSB-scores were 9 [interquartile range (IQR) = 5-14] and 16 (IQR = 9-23), respectively. Of the 59 patients, 54 received ≥ 1 cycle while 27 underwent post-C4 evaluation with detectable cfDNA levels in 18/27 (66.7%). No baseline characteristic correlated with cfDNA detectability. Median overall survival (OS) and progression-free survival (PFS) were 262 days and 167 days, respectively. ECOG PS ≥ 2, RSB-score > 9 and TSB-score > 16 were all associated with worse OS and PFS as was cfDNA detectability [median OS = 97 days vs. 298 days and median PFS = 97 days vs. 197 days; P = 0.025; hazard ratio (HR) = 2.17]. Conclusions: Baseline cfDNA detectability is independently associated with poor OS and PFS in patients with advanced sq-NSCLC on chemotherapy.